Effects of Wooden Dowel Species, Edge Banding Thickness, and Adhesive Types on Embedded Strength in Particleboard - Abdurrahman Karaman (Drvna Industrija, 2022)
Composite materials, edge banding, and wooden dowels are used in inner decoration and construction of furniture frames. However, there is little information available concerning the embedded strength of various fasteners and, in particular, dowels in these materials. The aim of this study was to determine the embedded strengths of PVC edge bandings with the thickness of 0.8, 1, and 2 mm, and dowels produced from five different wood species bonded parallel to the surfaces of a melamine coated particleboard (YL-Lam) with polyvinyl acetate (PVAc-D4) or polyurethane (PUR-D4). In accordance with TS 4539 standard, the effect of wooden dowel species, thickness of edge banding, and type of adhesives on embedded strength were determined. Embedded strength values of polyurethane (PUR-D4) were found 10 % higher than the embedded strength values of polyvinyl acetate (PVAc-D4). The highest embedded strength was obtained for beech dowel bonded with polyurethane (PUR-D4) adhesive in the samples with 0.8 mm PVC edge banding (2.004 N/mm2), while the lowest embedded strength was obtained for Scots pine dowel with polyvinyl acetate (PVAc-D4) adhesive in the samples without PVC edge banding (0.826 N/mm2). This value is higher than the predicted value that allows designers to estimate the embedded strength of dowels.